Analysis of the deterioration rule and perception mechanism of egg yolk powder odor based on volatile omics, molecular docking and molecular dynamics simulation - Jiahui Song; Enhui Ma; Renrui Zheng; Zhuohang Huang; Jun Jiang; Zhijie Bao; Songyi Lin (Food Research International, 2026)

Methoxycarbonylation of ethylene/ethane mixture to methyl propionate over Pd-phosphine system with H-Beta zeolite and sulfonic acid as acid promoters - Shaoxia Guo; Mengting Li; Liang Gao; Yongrui Wang; Cheng Gu; Longxiao Yang; Yuping Huang; Enhui Xing; Yibin Luo; Xinbin Ma; Xingtian Shu (Chemical Engineering Journal, 2026)

Effect of explicit intermediate layer on the solution accuracy of the thermal stress for printed circuit heat exchangers with the homogenization method - Xiaoxu Zhang; Zirui Xu; Enhui Li; Yin Tan; Jiyuan Bi; Dan Zheng; Sheng Wang; Ting Ma (Annals of Nuclear Energy, 2026)

Microbial Dark Matter, A Multi-layer Mystery - Xiaopan Ma; Enhui Wu; Yuanyuan Guo; Zheng Wei; Qianyi Zhou; Anita Voigt; Yijiang Liu; Xiaotao Shen; Lihui Feng; Shaymaa A. Ismail; Sridhar Mani; Mingguang He; et al. (Phenomics, 2026)

A novel compound nutrition powder ameliorates scopolamine-induced cognitive impairment via activating the PKA/CREB/BDNF signaling pathway and restoring cholinergic function - Xiaomeng Xu; Zihan Yuan; Enhui Ma; Limin Zhong; Dong Chen; Songyi Lin (Food Bioscience, 2026)

Enhanced acetate tolerance and resource recovery via adaptive evolution of Chlorella vulgaris for sustainable upcycling of organic wastewater - Weizhao Meng; Enhui Liu; Jiahao Ma; Yixi Su; Jingyan Hu; Xiaomin Liang; Weiqi Fu (Bioresource Technology, 2026)

Pulsed electric field technology as a strategy for achieving the synergistic effect of enhancing the safety and flavor quality of egg yolk liquid - Liu Dong; Enhui Ma; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Chemistry, 2026)

A review of weed image identification based on deep few-shot learning - Enhui Wu; Yu Chen; Ruijun Ma; Xiande Zhao (Computers and Electronics in Agriculture, 2025)

Whole-genome resequencing reveals selection signatures in China's first rainbow trout (Oncorhynchus mykiss) strain “Shuike No. 1” - Haibing Ma; Gaochao Wang; Tianqing Huang; Enhui Liu; Wei Gu; Gefeng Xu (Aquaculture, 2025)

K-modified cyano-rich carbon nitride for photocatalytic production of water treatment agent - Hydrogen peroxide in two-phase system - Yanhe Li; Zelin Ma; Yi Yang; Xia Li; Enhui Gao; Qiming Zhao; Xiao Chen; Hao Zhang (Journal of Water Process Engineering, 2025)

Holographic characterization of typical silicate minerals by terahertz time-domain spectroscopy - Haochong Huang; Xinyu Li; Zhiyuan Zheng; Hanhan Fan; Caiqin Liu; Enhui Yuan; Jialu Gu; Yutong Ma; Qian Xu; Spozmai Panezai; Shanshan Li; Zhuo Zhang; et al. (Applied Clay Science, 2025)

Spatial confinement of Co-N/O nanocatalyst into hollow carbon nanosphere for water purification and its biotoxicity assessment - Chen Fang; Yangyang Bai; Lingyuan Ma; Yejun Pan; Kun Pang; Jiaying Yan; Jiajun Song; Enhui Jiang; Haiyu Zhao; Chuanying Pan; Xiang Liu; Xianyong Lan (Chemical Engineering Journal, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

Effect of fly ash micromotors on expression of antibiotic resistance genes in straw composting - Jiaoyu Ren; Yanyan Cuan; Enhui Ma; Zhuxin Wang; Guangyuan Xie; Hong Wang (Journal of Environmental Chemical Engineering, 2024)

Development of polymorphic simple sequences repeats markers from whole gene resequencing data comparison of 68 Oncorhynchus mykiss - Haibing Ma; Tianqing Huang; Enhui Liu; Gaochao Wang; Wei Gu; Gefeng Xu (Frontiers in Marine Science, 2024)
Rainbow trout ( Oncorhynchus mykiss ) is a significant cold-water fish farmed in China. Currently, most molecular marker-assisted breeding applications in rainbow trout rely on SSR markers. Although many rainbow trout SSR markers have been developed, methods for mining many polymorphic SSR markers from the genome and identifying them efficiently and rapidly are still lacking. For this reason, this study used in silico simulation method to rapidly develop a large number of polymorphic SSR markers quickly. A total of 354,613 SSR loci with two to six nucleotide repeat motifs were mined from 32 chromosomes of the rainbow trout reference genome using GMATA. The chromosome sequences of the reference genome were then aligned to the whole genome sequencing data (10×) of 68 rainbow trout samples. In silico genotyping was performed using the HipSTR programme to compare and count the variation in the number of repeats of the motifs of the SSR loci in the samples. The loci with high deletion rates and monomorphism were discarded, while those with more than one non-reference allele were kept. The final set of polymorphic SSR loci screened was 78,828. Finally, 4,821 SSR loci were selected with more than 3 alleles and no deletion in all rainbow trout samples and were physically mapped. The average polymorphic information content of these loci was 0.692, indicating high levels of polymorphism. These SSRs were utilized to analyse the genetic diversity and population structure of the 68 rainbow trout samples. The results showed that these 68 samples were divided into two groups. These newly discovered polymorphic SSR markers will provide valuable information for evaluating the construction of rainbow trout family lines for genetic diversity and improvement.

Genome-wide identification of simple sequence repeats and development of polymorphic SSR markers in brown trout (Salmo trutta) - Haibing Ma; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang; Bingqian Wang; Jianshe Zhou; Gefeng Xu (Conservation Genetics Resources, 2023)

NaCl-induced expression of AtVHA-c5 gene in the roots plays a role in response of Arabidopsis to salt stress - Aimin Zhou; Enhui Liu; Hongping Ma; Shuang Feng; Shufang Gong; Jingang Wang (Plant Cell Reports, 2018)